A Win-Win Collaboration - Mary Beth Parkinson (Pennsylvania Libraries: Research & Practice, 2013)
This brief article reports on a collaborative book-borrowing policy between The Brendlinger Library of Montgomery County Community College and the Wissahickon Valley Public Library (WVPL), both located in Blue Bell, PA.  Beginning in January 2013, WVPL will donate books periodically to the Brendlinger Library in support of the students enrolled in Reading classes.  Circulation statistics will be reported to WVPL, and the books will be returned to WVPL for sale in the WVPL Friends of the Library book sale. Keywords: academic library; public library,  community college library; collaboration; developmental readers; reading programs; reading instruction; literacy; Montgomery County Community College; Wissahickon Valley Public Library